Mucosa-Muscular Signaling for Bile-Induced Esophageal Dysmotility. An Experimental Study in Ex-Vivoguinea-Pig Isolated Esophagi - Rodrigo C. Souza; Fernando A. M. Herbella; Chandler Tahan; Alice T. Ferreira; Marcelo E. S. Rocha; Marco G. Patti (Journal of Digestive Disorders And Diagnosis, 2016)
Background/Aims: Esophageal motor abnormalities are frequently found in patients with gastroesophageal reflux disease. The effect of bile in esophageal dysmotility is probably secondary to mucosal signaling to the muscular layer and not a transmural process. This study aims to identify the mucosa-muscular signaling path by receptors blockage in an experimental study. Methods: Fifteenguinea pig esophagi were isolated and ex-vivo esophageal contractility was assessed with force transducers. The esophagi were incubated in 100 µM ursodeoxycholic acid for 1 hour and 5 sequential contractions induced by 40 mM KCl spaced by 5 minutes were measured. After 30 minutes, esophagi specimens were incubated in 3 different smooth-muscle contraction antagonists: atropine (1µM) in 5, suramin (1µM) in 5 and genistein (1µM) in 5. The same protocol for contractions was repeated. Values are expressed as mean ± standard deviation and encompass the mean of five stimuli. Experimental procedures were approved by the University Institutional Review Board. Results: Contraction amplitudes after bile incubation but before antagonist incubation were 1.6±0.6 g, 1.2±0.8 g, and 1.2±0.4 g for atropine, suramin and genistein, respectively. Mean contraction amplitudes after antagonists instillation were 1.2±0.6 g, 1.4±0.5 g, 0.9±0.2 g, respectively. There was no different in contraction amplitude before and after instillation of atropine (p=0.188), suramin (p=0.488) or genistein (p=0.079). Conclusion: Our results show that blockage of cholinergic (atropine), purinergic (suramin) or tyrosine kinase (genistein) paths do not change esophageal dysmotility induced by bile. Other molecular path may play the role in this scenario.
Keywords: Gastrointestinal motility